A Lebanese dietary pattern promotes better diet quality among older adults: findings from a national cross-sectional study - Jomaa, Lamis (BMC Geriatr, 2016)
BACKGROUND: Proper nutrition is critical for healthy aging and maintaining functional independence. Limited research has been done on the assessment of dietary patterns of older adults and their association with diet quality indices. This study was conducted to identify, characterize, and evaluate the dietary patterns and diet quality of older adults in Lebanon, a middle-income country undergoing nutrition transition. METHODS: A cross-sectional population-based study was conducted on a nationally representative sample of community-dwelling older adults aged >50 years (n = 525). Socio-demographic, anthropometric, and lifestyle variables were collected through interviews, and dietary intake was assessed using a semi-quantitative food frequency questionnaire (FFQ). Five commonly used diet quality indices (DQIs) were calculated, including the Alternative Healthy Eating Index (AHEI), the alternate Mediterranean diet score (aMed), the Dietary Approach to Stop Hypertension (DASH) style diet score, and the Lebanese Mediterranean Diet index. Dietary patterns (DPs) were derived using exploratory factor analysis. Associations of identified DPs with energy, energy-adjusted nutrients, and DQIs were evaluated by Pearson’s correlations. Multiple linear regression analyses were used to examine correlates of DPs. RESULTS: Three DPs were derived: Lebanese, Western, and High Protein/Alcohol patterns. The Lebanese pattern had highest correlations with fiber, folate, vitamin C, and all five DQIs. The Western was positively associated with energy and sodium and was inversely correlated with fiber, most vitamins, and a number of DQIs, namely AHEI, aMED, and DASH-style diet score. Highest correlations with intakes of proteins and fat were observed for the High Protein/Alcohol pattern. The Lebanese pattern was associated with female gender, education, nonsmoking and physical activity, whereas the Western pattern was associated with adverse health behaviors, including smoking, skipping breakfast, and physical inactivity. CONCLUSIONS: Of the three identified patterns, the Lebanese DP was associated with better diet quality and healthier lifestyle behaviors while the Western pattern implicated a lower quality diet. Public health programs promoting prudent diets, including the Mediterranean and Lebanese DPs, are needed to improve the diet quality of middle-aged and older adults in an attempt to improve their functionality and quality of life.